Hope and its relation to suicidal risk behaviors among Malaysian adolescents - Choon, Min Wai; Abu Talib, Mansor; Yaacob, Siti Nor; Tan, Jo Pei; Awang, Hamidin; Hassan, Sallahuddin; Ismail, Zanariah (Canadian Center of Science and Education, 2014)
Suicide is an epidemic issue worldwide and Asian countries are of no exception. In Malaysia, adolescent suicide constituted 10% of the overall reported suicide cases. Aforementioned, the current study examines Snyder’s theory of hope to understand suicidal risk among Malaysian adolescents. A total of 1441 adolescents were recruited using a multistage cluster sampling. Results showed significant relationship between both agency and pathway thinking with risk of suicidal behavior. Specifically, only agency thinking uniquely predicts adolescents’ suicidal risk in a regression model. Adolescents with higher motivation towards accomplishing a goal or plan have lower risk engaging in suicidal behaviors. Thus, suicide prevention focusing on increasing hope is significantly important. Limitations were discussed in the study.